Japanese foreign exchange intervention and the Yen/Dollar exchange rate: a simultaneous equations approach using realized volatility - Eric Hillebrand; Gunther Schnabl; Yasemin Ulu (Center for Economic Studies and ifo Institute (CESifo), 2006)
We use realized volatility to study the influence of central bank interventions on the yen/dollar exchange rate. Realized volatility is a technical innovation that allows specifying a system of equations for returns, realized volatility, and interventions without endogeneity bias. We find that during the period 1995 through 1999, interventions of the Japanese monetary authorities did not have the desired effect with respect to the exchange rate level and we measure an increase in volatility associated with interventions. During the period 1999 through 2004, the estimations are consistent with successful interventions, both in depreciating the yen and in reducing exchange rate volatility.
Keywords: C32; E58; F31; F33; G15; 330